Are the Final Semester Examination Questions for Basic Science Concepts Made by Lecturers Have the Quality According to the Rasch Model? - Anasufi Banawi; Muhammad Irfan Rumasoreng; Irawati Basta; Adam Latuconsina (Jurnal Prima Edukasia, 2023)
Analysis of Final semester examination items in the Basic Science Concepts course using the Rasch model has not been widely carried out, even though analyzing subject matter test items is a reflection of education and a noble task that can be carried out by educators in order to perfect and improve the quality of the tests they make themselves. The Rasch model is chosen so that the quality of the items does not depend on the test taker's ability to respond to answers. This study aims to describe the quality of the items from the Final Semester Examination on Basic Science Concepts course using the Rasch model. In this research used descriptive method. Data were collected through a documented study of 10 multiple choice questions in the form of answer sheets from 42 (6 male; 36 female) students of Madrasah Ibtidaiyah Teacher Education (PGMI) at a state university in Ambon. The Rasch model with the help of the Winstep software program is used in analyzing the items. The results showed that a number of items according to the Rasch model with test reliability were in the high category. Existing results can be used by lecturers as diagnostic material for achieving student knowledge competence and improving lectures.